A new species of Allorhogas (Hymenoptera: Braconidae: Doryctinae) reared from galls on Lycium cestroides Schltdl. (Solanaceae) in Argentina - Martinez, Juan Jose (2011)
Allorhogas cordobensis sp. nov. (Hymenoptera: Braconidae: Doryctinae) is described from the province of Córdoba, Argentina. Its representatives can be distinguished from all other known species of the genus by the unusual morphology of the ovipositor tip and the expanded clypeus apically. Remarkably, this species is also characterized by having a tridentate mandible, a feature known only in exodont braconids, mostly of the subfamily Alysiinae. The new species was reared from stem galls on Lycium cestroides, which constitutes the second record of an Allorhogas species associated with galls on representatives of the plant family Solanaceae.